2015
DOI: 10.1200/jco.2015.62.2035
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Surveillance Intervals in Familial Colorectal Cancer

Abstract: In view of the relatively low rate of AAPs at 6 years and the absence of CRC in group A, we consider a 6-year surveillance interval appropriate. A surveillance interval of 3 years might be considered in patients with AAPs and patients with ≥ three adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 33 publications
3
27
0
2
Order By: Relevance
“…Still, the proper interval between colonoscopies is a matter of debate,1 7 8 12–16 as is whether families with a less striking phenotype benefit from colonic surveillance 17 18…”
Section: Introductionmentioning
confidence: 99%
“…Still, the proper interval between colonoscopies is a matter of debate,1 7 8 12–16 as is whether families with a less striking phenotype benefit from colonic surveillance 17 18…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that five-or six-year examination intervals from the age of 45 are sufficient in most cases of FCRC [7][8][9]. Findings at the individual's first colonoscopy may also provide tools to customise future surveillance [30].…”
Section: Improving Surveillance In the Futurementioning
confidence: 99%
“…Findings at the individual's first colonoscopy may also provide tools to customise future surveillance [30]. FCRC patients with pre-malignant high-risk adenomas may have shorter intervals, and older individuals without alarming initial findings might not need continued surveillance [7,8].…”
Section: Improving Surveillance In the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Hennink et al from the Netherlands recently reported results from the Familial Colorectal Cancer Surveillance (FACTS) study, which attempts to address this conundrum (9). The study is a multicenter, prospectively randomized trial evaluating colonoscopy screening intervals for people with a family history of CRC.…”
mentioning
confidence: 99%